Empowering waste recycling through technology: A case study of the octopus social movement - Aldi A.M, Muhammad; Yuniarti, Tatik; Samariansyah, Iwan (Social, Ecology, Economy for Sustainable Development Goals Journal, 2025)
Background: Garbage is a serious problem that can have a negative impact on the environment and its surroundings, the large amount of waste produced in Bekasi reaches 6 million tons per year, making West Java one of the provinces with the most waste generation in 2022. This has become one of the triggers for the Octopus initiative in engage in social movements in the environmental field. Octopus is present in a new social movement by launching and developing a digital-based recycling waste management application. Based on these problems, this research is aimed at analyzing the Octopus social movement in managing recycled waste in the era of society 5.0. Methods: Based on these problems, this research is aimed at analyzing the Octopus social movement in managing recycled waste in the era of society 5.0. The method used is descriptive method with a qualitative approach. Findings: The results of the study explained that the new social movement carried out by Octopus was fairly effective, this was shown in the number of Octopus application users reaching nearly 200 thousand users spread across Jakarta, South Tangerang, Bandung, Bali and Makassar including Bekasi. This application also works with more than 1,700 unit waste banks and 14,600 scavengers who have been trained to become conservationists. Conclusion: Using applications is an effective alternative to mobilize people to be aware of environmental problems, especially waste issues. Novelty/Originality of this article: The novelty in this research is the use of technology used by Octopus in organizing the community